Economic analysis of suicide prevention : towards evidence-based policy-making /: towards evidence-based policy-making. ([2017]) - Sawada, Yasuyuki, 1967-; (College teacher), Ueda, Michiko; Matsubayashi, Tetsuya
No abstract available